Artist at small motherland - Дмитрий Сергеевич Будкеев (Культурное наследие Сибири, 2021)
In the article examines diary entries and memoirs of the People’s artist of the Russian Federation Mikhail Yakovlevich Budkeev. We consider the time in which the artist wrote a series of paintings dedicated to the nature and people of Virgin lands, the village Ovsyannikovo.